Endocannabinod Signal Dysregulation in Autism Spectrum Disorders: A Correlation Link between Inflammatory State and Neuro-Immune Alterations - Brigida, Anna Lisa (Int J Mol Sci, 2017)
Several studies highlight a key involvement of endocannabinoid (EC) system in autism pathophysiology. The EC system is a complex network of lipid signaling pathways comprised of arachidonic acid-derived compounds (anandamide, AEA) and 2-arachidonoyl glycerol (2-AG), their G-protein-coupled receptors (cannabinoid receptors CB1 and CB2) and the associated enzymes. In addition to autism, the EC system is also involved in several other psychiatric disorders (i.e., anxiety, major depression, bipolar disorder and schizophrenia). This system is a key regulator of metabolic and cellular pathways involved in autism, such as food intake, energy metabolism and immune system control. Early studies in autism animal models have demonstrated alterations in the brain’s EC system. Autism is also characterized by immune system dysregulation. This alteration includes differential monocyte and macrophage responses, and abnormal cytokine and T cell levels. EC system dysfunction in a monocyte and macrophagic cellular model of autism has been demonstrated by showing that the mRNA and protein for CB2 receptor and EC enzymes were significantly dysregulated, further indicating the involvement of the EC system in autism-associated immunological disruptions. Taken together, these new findings offer a novel perspective in autism research and indicate that the EC system could represent a novel target option for autism pharmacotherapy.